PENGARUH STRATEGI THINK TALK WRITE (TTW) TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS II SDN 79 PEKANBARU - Vopy Dwi Zasria; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to description poetry writing skills difference between the experimental class and control class. This research is a quasi-experimental research with design research "nonequivalent control group design". The sample in this research was class II SDN 79 Pekanbaru as many as 29 people. Analysis of the data used to analyze the results of the research are different test (t-test). Based on the results of data analysis can be concluded that there is no significant difference between the skill of writing poetrystudents experiment class with the control class because after Mann Whitney test score gains of students in the experimental class and control class with significance level α = 0.05 meets the criteria Zhitung <Ztabel namely 1.76 <1.96 means there are no significant differences between the skill of writing poetry students experiment class with the control class. However, the hypothesis in this research proved that there are effect of talk think write strategy to poetry writing skills of students. This is proved by the results of the test count determinant coefficient is known that the coefficient r (xy) on writing skills by using a strategy talk think write is 0.3959 and R2 of 16%, this suggests that strategies talk think write affect poetry writing skills of students by 16%, while the coefficient r (xy) on poetry writing skills of students using conventional learning is 0.1216 with a determinant (R) of 1.5% this suggests that strategies talk think write affect poetry writing skills of students by 16%. It is mean the talk think write strategy a positive influence on poetry writing skills of class II SDN 79 Pekanbaru.Key Words: talk think write strategy (TTW), writing poetry skill